The Enduring Impact of What Clinicians Say to People With Low Back Pain - Darlow, Ben (American Academy of Family Physicians, 2013)
PURPOSE: The purpose of this study was to explore the formation and impact of attitudes and beliefs among people experiencing acute and chronic low back pain. METHODS: Semistructured qualitative interviews were conducted with 12 participants with acute low back pain (less than 6 weeks’ duration) and 11 participants with chronic low back pain (more than 3 months’ duration) from 1 geographical region within New Zealand. Data were analyzed using an Interpretive Description framework. RESULTS: Participants’ underlying beliefs about low back pain were influenced by a range of sources. Participants experiencing acute low back pain faced considerable uncertainty and consequently sought more information and understanding. Although participants searched the Internet and looked to family and friends, health care professionals had the strongest influence upon their attitudes and beliefs. Clinicians influenced their patients’ understanding of the source and meaning of symptoms, as well as their prognostic expectations. Such information and advice could continue to influence the beliefs of patients for many years. Many messages from clinicians were interpreted as meaning the back needed to be protected. These messages could result in increased vigilance, worry, guilt when adherence was inadequate, or frustration when protection strategies failed. Clinicians could also provide reassurance, which increased confidence, and advice, which positively influenced the approach to movement and activity. CONCLUSIONS: Health care professionals have a considerable and enduring influence upon the attitudes and beliefs of people with low back pain. It is important that this opportunity is used to positively influence attitudes and beliefs.